Pd(II)-Catalyzed para-Selective C–H Arylation of mono-Substituted Arenes - Wang, Xisheng (2011)
Pd-catalyzed para-selective C–H arylation of mono-substituted arenes including toluene is developed for the first time using F(+) as a bystanding oxidant. This finding provides a new retrosynthetic disconnection for biaryl synthesis.